Co‐design of a patient and family‐initiated escalation of care intervention to detect and refer patient deterioration: Research protocol. (8th April 2020) - McKinney, Aidín; Fitzsimons, Donna; Blackwood, Bronagh; White, Mark; McGaughey, Jennifer
Abstract: Aim: To co‐design a patient and family‐initiated intervention to improve the detection and escalation of patient deterioration on acute adult hospital wards in Northern Ireland and the Republic of Ireland. Design: The design is a collective case study approach in an acute hospital in Northern Ireland and the Republic of Ireland using an adapted co‐design approach and Medical Research Council framework guidelines. Methods: Data will be collected from key stakeholders (patients, relatives, and healthcare professionals) using individual and focus group interviews and a review of patients' records. This will inform the development of a co‐designed intervention and implementation strategy. The developed prototype will be further refined and optimized following a feedback session with stakeholders from each hospital site. This study was funded in February 2018 and Research Ethics Committee approval was granted in March 2019. Discussion: This study will contribute to the growing knowledge base in relation to the interventions that improve the escalation of patient deterioration. It will also contribute to the intelligence, evidence and understanding of the role of patient and family participation in the detection and referral of clinical deterioration in acute adult hospital settings. Impact: There is an ongoing need to introduce systems or mechanisms in acute care hospital settings which allow patient or family members to have a greater role in escalating care when they are concerned about patient deterioration. To date there is limited evidence of rigorous studies examining this area and this study will use stakeholder engagement and involvement to co‐design an intervention which will provide patients and families with a mechanism to address concerns which can be tested in practice. Abstract : 目的: 共同设计一个由患者和家庭发起的干预措施, 以改进北爱尔兰和爱尔兰共和国急症病房成年患者病情恶化的探测和升级。 设计: 该设计是在北爱尔兰和爱尔兰共和国的一家急症医院中采用的一种集体病例研究方法, 采用经调整的共同设计方法和医学研究理事会框架指南。 方法: 通过个人和焦点小组访谈以及检查患者的病历, 从主要利益相关者那里(患者、亲属和医疗保健人员)收集数据。这将有助于制定共同设计的干预和实施策略。在与各医院的利益相关者进行反馈后, 进一步完善并优化所开发的原型。本研究于2018年2月获得资助, 于2019年3月获得研究伦理委员会的批准。 讨论: 该研究将有助于扩充改善患者病情恶化升级的干预措施的相关知识库。也将有助于提供患者和家庭在参与成人急症医院环境中发现和转诊临床恶化病例方面的信息、证据及相关作用。 影响: 目前需要在急症医院环境中引入系统或机制, 使患者或家庭成员在关注患者病情恶化时能够在提升护理水平方面发挥更大的作用。迄今为止, 对这一领域进行严格研究的证据有限, 本研究将利用利益相关者的参与和关注, 共同设计一个干预措施, 为患者和家庭提供解决实践中检验问题的机制。